Neonatal Empyema Thoracis - Mazumdar, J; Sen, S (Journal of Nepal Paediatric Society, 2014)
Empyema thoracis, is a rare cause of respiratory distress in neonates. Only a few cases of neonatal empyema thoracis are described in medical literature. Empyema thoracis is not a well known entity in the neonates. It is fulminant with rapid progression with a high mortality. Compounding the problem is its uncertain etiopathogenesis and lack of definite treatment guidelines. We shall describe one case of neonatal empyema in a newborn aged five days caused by Pseudomonas aeruginosa. The neonate died subsequently. DOI: http://dx.doi.org/10.3126/jnps.v34i1.8233 J Nepal Paediatr Soc 2014;34(1):65-67